POLITENESS IN BUGINESE WEDDING CEREMONY - Ulfah Ridhwan Dirham (Universitas Nasional, 2022)
One of the cultural elements of communication that must be considered is politeness. Politeness is indispensable in communication, especially in Southeast Asian cultures, which have degrees of politeness. As cultural aspects affect the communicative language, politeness would be expected in society. One of the politeness implementations is the polite language used in the Buginese traditional wedding ceremony. In order to reveal politeness and its strategies in the traditional Buginese wedding ceremony, the study employed a qualitative method with observation and analytical descriptive approach by examining the politeness strategies and conversational language used in the Buginese wedding ceremony processions. The data were obtained from the video recordings of the wedding ceremony and the interviews with four newlyweds. The result showed that positive politeness strategies were predominantly used in the Buginese wedding ceremony. The study also revealed that the positive politeness strategies were closely connected to the cultural values of South Sulawesi, which showed a strict sequence of the traditional wedding ceremony that must be followed. The sequence symbolizes the tie that binds two human beings in goodness and beneficence, which must be conducted religiously. The study concludes that the language used during the traditional Buginese wedding ceremony adhered to the positive politeness principle, although the nature of the language was conversational. Keywords: politeness, politeness strategy, polite conversational language, Buginese wedding ceremony.